Math, asked by zhaibinlondon, 5 months ago

only (c) show that f(x)=4x-6
please help....​

Attachments:

Answers

Answered by harshvardhanyadav422
0

Answer:

a) 14

b) 3x-1

Step-by-step explanation:

a) put the value of x = 8 in f(x) = 2(x-1)

2(8 - 1) \\  = 2 \times 7 \\  = 14

b)

g( {g}^{ - 1} x )= x  \\ now \: the \: value \: ({g}^{ - 1} x) \: in \: the \: place \: of \: x

so

g ({g}^{ - 1} x) = ({g}^{ - 1} x + 1) \div 3 \\ also \: g ({g}^{ - 1} x) \:  = x \\  \\ so \:  \:  \:  \: x = ({g}^{ - 1} x + 1) \div 3 \\  \\ 3x = {g}^{ - 1} x + 1 \\  \\ {g}^{ - 1} x = 3x - 1 \\  \\ your \: answer \: is \: 3x - 1.

HOPE IT HELPS

Similar questions